Training Status and Adoption of Marketing Channels by Members of Self-Help Group - Maurya, Abhilash Singh; Mishra, Ayush; Joginder Singh Mailk,; Bhavesh,; Ram Niwas, (Indian Journal of Extension Education, 2024)
The study was undertaken in 2022 in Bundelkhand region of Uttar Pradesh to assess the training status, adoption of marketing channels, and effect of the socio-personal and economic profile of SHG members on their training level and marketing channel adoption. The findings revealed that the majority of SHG members were small and marginal farmers who exhibited medium to high levels of social exposure, mass-media use, and social participation. The majority of the respondents had participated in some training programme, held at a nearby place. Individual sales and group sales were the most preferred marketing channel adopted by SHG members. Higher education, social contacts, and media exposure were found to be associated with a higher level of training and higher adoption of diverse marketing channels. The study advocates the need for specialized and need-based training programmes for SHG members to increase their participation and adoption of group marketing to gain leverage through economies of scale.